Atrial fibrillation in patients with haemophilia: a cross‐sectional evaluation in Europe. (14th April 2014) - Schutgens, Roger E. G.; Klamroth, R.; Pabinger, I.; Malerba, M.; Dolan, G.; ,
Summary: Atrial fibrillation (AF) is a common health problem in the general population, but data on prevalence or management in patients with haemophilia (PWH) are lacking. The aims of this study were to analyse the prevalence of AF and risk factors for stroke using a cross‐sectional pan‐European design and to document current anticoagulation practice. The ADVANCE Working Group consists of members from 14 European haemophilia centres. Each centre retrieved data on their PWH with AF. From the total of 3952 adult PWH, 33 had AF with a mean age of 69 years (IQR 62–76). Haemophilia was severe in seven (21%), moderate in six (18%) and mild in 20 (61%) patients. The overall AF prevalence was 0.84% and increased with age; 0.42% in patients 40–60 years and 3.4% in patients >60 years. The mean CHA2 DS2 ‐Vasc score was 1.3 (range 0–4), predominantly determined by age and hypertension. Hypertension was reported in 48% of PWH with AF. In 11 patients (33%), anticoagulation was started of whom nine aspirin and two vitamin K antagonists. Of these 11 patients, nine had mild haemophilia. Anticoagulation was given in 42% of patients with a CHA2 DS2 ‐Vasc score ≥2. During follow‐up (mean 57 months), there were no thrombotic events reported, nor increases in bleeding severity. The prevalence of AF in haemophilia increases with age and is predominantly present in mild haemophilia. PWH have a low stroke risk based on their CHA2 DS2 ‐Vasc scores, that might be even lower considering the hypocoagulable state. Only 33% of PWH with AF receives any form of anticoagulation therapy.